2014
DOI: 10.4314/jab.v74i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzylaminopurine on <i>in vivo</i> multiplication of French plantain (<i>Musa</i> spp. AAB) cv. ‘Itoke sege’

Abstract: However, the response of cv. "Itoke Sege" to in vivo macropropagation combined with different benzylaminopurine (BAP) concentrations is not known. This study was conducted to determine the appropriate concentration of BAP for enhancing in vivo macropropagation of French plantain cv. 'Itoke Sege'. Methodology and results: Sword suckers of about 70 -80 cm tall and 14 -16 cm collar diameter were obtained from farmers' fields in Rungwe district in Mbeya, Tanzania. Moistened sawdust was steamsterilized for 45 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Comparatively, a temporary treatment of deshealthed corms of plantain cv. "Itoke Sege" in benzylaminopurine at 1.5 mg /litre produced 17.11 in vivo suckers per corm (Kindimba and Msogoya, 2014). In the present study TDZ concentration from 0.5 to 2.0 mg/l increased in vivo shoot growth based on the number of leaves per shoots though the number of leaves per sucker decreased as TDZ concentration increased to 3.0 mg/l.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Comparatively, a temporary treatment of deshealthed corms of plantain cv. "Itoke Sege" in benzylaminopurine at 1.5 mg /litre produced 17.11 in vivo suckers per corm (Kindimba and Msogoya, 2014). In the present study TDZ concentration from 0.5 to 2.0 mg/l increased in vivo shoot growth based on the number of leaves per shoots though the number of leaves per sucker decreased as TDZ concentration increased to 3.0 mg/l.…”
Section: Discussionsupporting
confidence: 40%
“…The technique involves disinfecting, deshealthing banana corms to expose axillary buds and decorticating the apical meristem to suppress Journal of Applied Biosciences 81:7214 -7220 ISSN 1997-5902 apical dominance (Kwa, 2003;Njukwe et al, 2005;Kindimba and Msogoya, 2014). Compared to in vitro propagation, this technique provides in a short period pest-free plantlets (Njukwe et al, 2005;Kwa, 2003) and has the potential of producing 50 -60 shoots per corm in 4 -5 months (Baiyeri and Aba, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An innovative micropropagation technique for raising plantlets is tissue culture [17]- [20]; however, this procedure requires high initial investment costs for specialised laboratories. In contrast, a macropropagation technique that is now commonly employed by many smallholder plantain and banana farmers in Sub-Saharan Africa is the Plants Issus de Fragments de tige (PIF) treatment [13], [16], [21] that destroys the apical meristem with a crosswise incision and leads to robust and healthy plantlets at the nursery stage [5]. This is especially the case, when pest (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…banana weevil and nematodes) infested suckers and corms are treated with hot water at 52°C for 20 min prior to planting [11], [22]. Moreover, the PIF technique in combination with synthetic or natural plant growth regulators has increased the number of shoots per corm [21]. Despite several studies having demonstrated that large numbers of clean and healthy plantlets can be produced by macropropagation, there are only few data available on the performance of that planting material under typical farming conditions [23].…”
Section: Introductionmentioning
confidence: 99%